SYSTEMATIC ANALYSIS OF HONEY PLANTS IN THE SURKHANDARYA REGION - N. T. Atamuratova; D. M. Alikarieva (Bright Mind Publishing, 2025)
This study presents a systematic analysis of the species composition of wild honey plants in the Surkhandarya region (southern Uzbekistan). The geographical and ecological characteristics of the distribution of honey plants are examined, along with their taxonomic structure and importance for the development of beekeeping. The number of families, genera, and species is determined, the life forms of honey plants are described, and their forage value is assessed. The data obtained can serve as a basis for the rational use of the region’s honey plant resources.
Keywords: Honey plants, species composition, plant communities, beekeeping, flora of Uzbekistan, nectar productivity